Mechanism for the failure of the Edwards hypothesis in the Sherrington-Kirkpatrick spin glass - EASTHAM, PAUL (My University, 2006)
The dynamics of the Sherrington-Kirkpatrick model at T=0 starting from random spin configurations is considered. The metastable states reached by such dynamics are atypical of such states as a whole, in that the probability density of site energies, p , is small at =0. Since virtually all metastable states have a much larger p 0 , this behavior demonstrates a qualitative failure of the Edwards hypothesis. We look for its origins by modeling the changes in the site energies during the dynamics as a Markov process. We show how the small p(0) arises from features of the Markov process that have a clear physical basis in the spin glass, and hence explain the failure of the Edwards hypothesis.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; spin glass; Sherrington-Kirkpatrick; Edwards hypothesis